Anti-static polyamide fabric and production process thereof

By introducing modifiers such as sulfonic acid groups and zinc oxide to graphene, a firm combination with polyamide fiber is solved, and the antistatic properties and moisture absorption of polyamide fabrics are significantly improved. performance.

CN119392428AInactive Publication Date: 2025-02-07ANHUI YISHANG TEXTILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411574325.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The chemical inertia and hydrophobicity of graphene in existing anti-static polyamide fabrics limits its interface bonding with polyamide fabrics, affecting the anti-static properties.

Method used

By introducing modifiers such as sulfonic acid groups and zinc oxide, the modified graphene forms a firm conductive cladding layer with the surface of the polyamide fiber to build a three-dimensional conductive network to improve interface binding force and anti-static properties.

Benefits of technology

It significantly improves the antistatic properties and durability of polyamide fabrics, and enhances its hygroscopic properties, effectively avoiding the accumulation and generation of static charges.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005121377360000091
    Figure BDA0005121377360000091
Patent Text Reader

Abstract

The invention discloses an anti-static polyamide fabric and a production process thereof, and belongs to the technical field of textile fabrics, the production process comprises the following steps: step S1, stirring polyamide fibers and modified graphene at 70-80 DEG C for reaction to obtain conductive fibers; s2, adding a modified antistatic aid and conductive fibers into tetrahydrofuran, performing ultrasonic dispersion, adjusting the pH value to 3-5 with hydrochloric acid, performing a reaction at 50-60 DEG C for 1-2 h, performing filtration, washing and drying, performing carding and twisting to form yarns, and performing warp and weft interweaving to obtain the antistatic polyamide fabric, the modified graphene with hydrophilic performance and the antistatic auxiliary agent with good moisture absorption performance are introduced, so that the compatibility and the interface bonding force of the modified graphene and the polyamide fiber are effectively enhanced, the polyamide fabric is endowed with good moisture absorption performance, and under the synergistic effect of the modified graphene and the antistatic auxiliary agent, the antistatic performance of the polyamide fabric is improved; and the antistatic durability is also enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of textile fabrics, and in particular relates to an antistatic polyamide fabric and a production process thereof. Background Art

[0002] In the process of textile production, the presence of static electricity can cause yarns to become tangled, affecting normal processing and production. In addition, the static electricity generated by the textiles when worn can cause a tingling sensation, reducing the comfort of wearing. What is more serious is that in special occasions, static electricity may cause fires, explosions, etc., endangering people's lives and property safety.

[0003] In the prior art, when preparing antistatic polyamide fabrics, graphene is usually added as an antistatic filler. Graphene has excellent conductivity and can accelerate the dissipation rate of surface charge of polyamide fabrics through electron migration performance, thereby improving the antistatic performance of polyamide fabrics. However, the graphene surface is hydrophobic and lacks active groups, has extremely high chemical inertness, and has poor bonding strength with polyamide fabrics, which limits its application in the antistatic application of polyamide fabrics. Therefore, how to improve the activity of graphene and the interfacial bonding strength with polyamide fabrics is a technical problem that needs to be solved at present. Summary of the invention

[0004] The object of the present invention is to provide an antistatic polyamide fabric and a production process thereof to solve the problems in the background technology.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A production process of antistatic polyamide fabric comprises the following steps:

[0007] Step S1, preparation of conductive fibers:

[0008] Add modified graphene to deionized water, disperse it by ultrasonic, add polyamide fiber, mix well, adjust pH value to 3-4 with hydrochloric acid, react at 70-80° C. with stirring for 1-2 hours, filter, wash and dry to obtain conductive fiber;

[0009] Step S2: Preparation of antistatic polyamide fabric:

[0010] Add modified antistatic additive and conductive fiber to tetrahydrofuran, after ultrasonic dispersion, adjust the pH value to 3-5 with hydrochloric acid, and react at 50-60°C for 1-2h. After filtering, washing and drying, combing and twisting to form yarn, and then interweaving warp and weft to obtain antistatic polyamide fabric.

[0011] Among them, the usage ratio of deionized water, modified graphene and polyamide fiber in step S1 is 500mL: 0.5-3g: 25-30g; the usage ratio of tetrahydrofuran, modified antistatic additive and conductive fiber in step S2 is 500mL: 1.6-2.3g: 20-25g.

[0012] Furthermore, the modified graphene is prepared by the following steps:

[0013] A1. Add p-aminoazobenzene-4-sulfonic acid and sodium nitrite to deionized water, mix well, cool to 0-5°C, add concentrated hydrochloric acid dropwise, perform diazotization reaction at 0-5°C for 2-3h, add graphene aqueous dispersion, pre-react at 5-10°C for 2h, and then react at room temperature for 7-9h. After filtering, washing with anhydrous ethanol and drying, an intermediate is obtained.

[0014] A2, adding the intermediate to the ethanol solution of zinc acetate, stirring and immersing for 15-20 minutes, filtering and drying, placing in deionized water, adding zinc acetate and hexamethylenetetramine after ultrasonic dispersion, reacting at 80-90° C. for 1-3 hours, filtering, washing and drying, and obtaining modified graphene;

[0015] The invention uses aminoazobenzene-4-sulfonic acid as a reaction monomer, performs a diazotization reaction with sodium nitrite under acidic conditions to form a diazonium salt, and then performs a coupling reaction with the diazonium salt through the electron-withdrawing effect of graphene, and grafts the diazonium salt onto the surface of graphene in the form of a covalent bond to obtain a graphene intermediate containing a sulfonic acid group. The chemical inertness of the graphene is improved by the introduction of the sulfonic acid group, and a chemical active site is provided for the grafting reaction of the modified graphene, and good hydrophilicity is given to the modified graphene. The invention first performs an immersion treatment on the intermediate with a low-concentration zinc acetate ethanol solution, and zinc oxide seeds are introduced on the surface of the intermediate through the complexation of the sulfonic acid group with zinc ions, and then zinc acetate is supplemented, and hexamethylenetetramine is used as a stabilizer and a promoter to promote the uniform growth of the zinc oxide seeds, so as to obtain the sulfonated modified graphene loaded with zinc oxide.

[0016] Furthermore, the usage ratio of the deionized water, p-aminoazobenzene-4-sulfonic acid, sodium nitrite, concentrated hydrochloric acid, and graphene aqueous dispersion is 50 mL: 2.5-3.1 g: 0.8 g: 8.4-9.3 mL: 60 mL; and the concentration of the concentrated hydrochloric acid is 75%.

[0017] Furthermore, the dosage ratio of the zinc acetate ethanol solution, the intermediate, deionized water, zinc acetate, and hexamethylenetetramine is 40 mL: 13.3-15.6 g: 80 mL: 5.2-7.6 g: 1-2 g; the concentration of the zinc acetate ethanol solution is 4.39-5.12 wt %; first using low-concentration zinc acetate to form zinc oxide seeds on the surface of the intermediate can help to form stable and uniform zinc oxide on the surface of the intermediate, avoiding the accumulation and agglomeration of zinc oxide due to rapid saturation at high concentrations, resulting in uneven growth of zinc oxide, which affects the conductive properties of the modified graphene.

[0018] Furthermore, the graphene aqueous dispersion is prepared by dispersing sodium dodecylbenzene sulfonate and graphene in 150 mL of deionized water at a mass ratio of 60:12.7-14.3, followed by ultrasonic treatment for 30 minutes.

[0019] Furthermore, the modified antistatic auxiliary agent is prepared by the following steps:

[0020] Add acrylonitrile, glycidyl methacrylate, allyl polyoxyethylene ether and sodium p-styrene sulfonate to acetonitrile, stir and mix, add azobisisobutyronitrile, react at 70°C for 2-3h, perform rotary evaporation, cool and solidify, grind, rinse with anhydrous ethanol, and then dry to obtain a modified antistatic additive;

[0021] With acetonitrile as solvent, acrylonitrile, glycidyl methacrylate, allyl polyoxyethylene ether and sodium p-styrene sulfonate as reaction monomers, under the action of initiator azobisisobutyronitrile, multi-polymerization is carried out through carbon-carbon double bonds to obtain anionic modified antistatic additives containing polar groups such as sulfonic acid group, nitrile group, ether oxygen bond and the like on the molecular chain.

[0022] Furthermore, the usage ratio of acetonitrile, acrylonitrile, glycidyl methacrylate, allyl polyoxyethylene ether, sodium p-styrene sulfonate and azobisisobutyronitrile is 80 mL: 6.7-7.4 mL: 13.5-14.2 mL: 9.2-9.6 mL: 20.6-21.2 g: 1.2 g.

[0023] The invention discloses an antistatic polyamide fabric, which is prepared by the above production process.

[0024] Beneficial effects of the present invention:

[0025] The modified graphene molecule surface of the present invention contains sulfonic acid groups, which can be combined with amino groups on polyamide molecular chains through ionic bonds under acidic conditions, and the modified graphene is grafted on the surface of polyamide fibers to form a firm conductive coating layer, thereby improving the affinity and interface bonding strength between the modified graphene and the polyamide fibers. In addition, the modified graphene molecule surface is also loaded with zinc oxide with good conductive properties, which can build a three-dimensional conductive network on the surface of the polyamide fibers, increase the channels for static charge leakage and dissipation, and effectively avoid the accumulation of static charge. When the polyamide fabric generates static electricity due to friction, the static charge can be quickly transmitted and discharged through the conductive network. Dew, thereby quickly eliminating static charge, giving the polyamide fabric good antistatic performance; at the same time, the modified antistatic auxiliary agent molecule of the present invention contains an epoxy group, which can react with the sulfonic acid group to form a ring-opening reaction and bind to the conductive fiber molecule, and improves the absorption of water in the air through polar groups such as nitrile groups and ether oxygen bonds in its molecules, which can not only give the polyamide fabric good hygroscopicity and softness, but also form a conductive liquid layer on the surface of the polyamide through a microscopic water film, and effectively inhibit the generation of static charge through the ability of the carbonyl group in the ether oxygen component to accept protons, thereby further improving the antistatic performance of the polyamide fabric;

[0026] The present invention introduces modified graphene with hydrophilic properties and an antistatic auxiliary agent with good hygroscopic properties, thereby effectively enhancing the compatibility and interfacial bonding force between the modified graphene and the polyamide fiber, and giving the polyamide fabric good hygroscopic properties. Under the synergistic effect of the two, not only the antistatic properties of the polyamide fabric are improved, but also the antistatic durability is enhanced. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] This embodiment provides a modified graphene, which is prepared by the following steps:

[0030] A1. Add 60 g of sodium dodecylbenzene sulfonate and 12.7 g of graphene to 150 mL of deionized water, and disperse by ultrasonic for 30 min to obtain a graphene aqueous dispersion.

[0031] A2. Add 2.5 g of p-aminoazobenzene-4-sulfonic acid and 0.8 g of sodium nitrite to 50 mL of deionized water, mix well, cool to 0 ° C, and then drop 8.4 mL of concentrated hydrochloric acid with a concentration of 75%, and diazotize at 0 ° C for 2 h. Then add 60 mL of graphene aqueous dispersion, pre-react at 5 ° C for 2 h, and then react at room temperature for 7 h. After filtering, washing with anhydrous ethanol and drying, an intermediate is obtained;

[0032] A3. Add 13.3 g of the intermediate to 40 mL of 4.39 wt% ethanol solution of zinc acetate, stir and soak for 15 min, filter and dry, place in 80 mL of deionized water, add 5.2 g of zinc acetate and 1 g of hexamethylenetetramine after ultrasonic dispersion, react at 80 ° C for 1 h, filter, wash and dry to obtain modified graphene.

[0033] Example 2

[0034] This embodiment provides a modified graphene, which is prepared by the following steps:

[0035] A1. Add 60 g of sodium dodecylbenzene sulfonate and 13.4 g of graphene to 150 mL of deionized water, and disperse by ultrasonic for 30 min to obtain a graphene aqueous dispersion.

[0036] A2. Add 2.8 g of p-aminoazobenzene-4-sulfonic acid and 0.8 g of sodium nitrite to 50 mL of deionized water, mix well, cool to 3 ° C, then drop 8.8 mL of concentrated hydrochloric acid with a concentration of 75%, diazotize at 3 ° C for 2.5 h, add 60 mL of graphene aqueous dispersion, pre-react at 7 ° C for 2 h, and then react at room temperature for 8 h. After filtering, washing with anhydrous ethanol and drying, an intermediate was obtained;

[0037] A3. Add 14.5 g of the intermediate to 40 mL of 4.39 wt% ethanol solution of zinc acetate, stir and soak for 15 min, filter and dry, place in 80 mL of deionized water, add 6.2 g of zinc acetate and 1 g of hexamethylenetetramine after ultrasonic dispersion, react at 80 ° C for 1 h, filter, wash and dry to obtain modified graphene.

[0038] Example 3

[0039] This embodiment provides a modified graphene, which is prepared by the following steps:

[0040] A1. Add 60 g of sodium dodecylbenzene sulfonate and 14.3 g of graphene to 150 mL of deionized water, and disperse by ultrasonic for 30 min to obtain a graphene aqueous dispersion.

[0041] A2. Add 3.1 g of p-aminoazobenzene-4-sulfonic acid and 0.8 g of sodium nitrite to 50 mL of deionized water, mix well, cool to 5 ° C, then drop 9.3 mL of concentrated hydrochloric acid with a concentration of 75%, diazotize at 5 ° C for 3 h, add 60 mL of graphene aqueous dispersion, pre-react at 10 ° C for 2 h, and then react at room temperature for 9 h. After filtering, washing with anhydrous ethanol and drying, an intermediate is obtained;

[0042] A3. Add 15.6 g of the intermediate to 40 mL of 4.39 wt% ethanol solution of zinc acetate, stir and soak for 15 min, filter and dry, place in 80 mL of deionized water, add 7.6 g of zinc acetate and 1 g of hexamethylenetetramine after ultrasonic dispersion, react at 80 ° C for 1 h, filter, wash and dry to obtain modified graphene.

[0043] Comparative Example 1

[0044] Compared with Example 2, the difference is that the intermediate is not impregnated with the ethanol solution of zinc acetate, and the other raw materials and steps are the same.

[0045] Comparative Example 2

[0046] Compared with Example 2, the difference is that the operation of step A3 is not performed, and the intermediate is directly used as modified graphene, and the other raw materials and steps are the same.

[0047] Example 4

[0048] This embodiment provides a modified antistatic additive, which is prepared by the following steps:

[0049] Add 6.7 mL of acrylonitrile, 13.5 mL of glycidyl methacrylate, 9.2 mL of allyl polyoxyethylene ether and 20.6 g of sodium p-styrene sulfonate to 80 mL of acetonitrile, stir and mix, add 1.2 g of azobisisobutyronitrile, react at 70 ° C for 2 h, and after rotary evaporation, cooling and solidification, grinding, eluting with anhydrous ethanol, and then drying, a modified antistatic additive is obtained.

[0050] Example 5

[0051] This embodiment provides a modified antistatic additive, which is prepared by the following steps:

[0052] Add 7.1 mL of acrylonitrile, 13.8 mL of glycidyl methacrylate, 9.4 mL of allyl polyoxyethylene ether and 20.9 g of sodium p-styrene sulfonate to 80 mL of acetonitrile, stir and mix, add 1.2 g of azobisisobutyronitrile, react at 70 ° C for 2.5 h, and after rotary evaporation, cooling and solidification, grinding, eluting with anhydrous ethanol, and then drying, a modified antistatic additive is obtained.

[0053] Example 6

[0054] This embodiment provides a modified antistatic additive, which is prepared by the following steps:

[0055] Add 7.4 mL of acrylonitrile, 14.2 mL of glycidyl methacrylate, 9.6 mL of allyl polyoxyethylene ether and 21.2 g of sodium p-styrene sulfonate to 80 mL of acetonitrile, stir and mix, add 1.2 g of azobisisobutyronitrile, react at 70 ° C for 3 h, and after rotary evaporation, cooling and solidification, grinding, eluting with anhydrous ethanol, and then drying, a modified antistatic additive is obtained.

[0056] Example 7

[0057] This embodiment provides a production process of an antistatic polyamide fabric, comprising the following steps:

[0058] Step S1, preparation of conductive fibers:

[0059] 0.5 g of the modified graphene obtained in Example 1 was added to 500 mL of deionized water, and after ultrasonic dispersion, 25 g of polyamide fiber was added. After mixing evenly, the pH value was adjusted to 3 with hydrochloric acid, and then stirred for reaction at 70° C. for 1 h. After filtering, washing, and drying, a conductive fiber was obtained.

[0060] Step S2: Preparation of antistatic polyamide fabric:

[0061] Add 1.6 g of modified antistatic additive and 20 g of conductive fiber to 500 mL of tetrahydrofuran, and after ultrasonic dispersion, adjust the pH value to 3 with hydrochloric acid, and react at 50 ° C for 1 hour. After filtering, washing and drying, combing and twisting to form yarn, and then interweaving by warp and weft to obtain antistatic polyamide fabric.

[0062] Example 8

[0063] This embodiment provides a production process of an antistatic polyamide fabric, comprising the following steps:

[0064] Step S1, preparation of conductive fibers:

[0065] 2 g of the modified graphene obtained in Example 2 was added to 500 mL of deionized water, and after ultrasonic dispersion, 28 g of polyamide fiber was added. After mixing evenly, the pH value was adjusted to 3.5 with hydrochloric acid, and then stirred for reaction at 75 ° C for 1.5 h, and then filtered, washed, and dried to obtain conductive fibers;

[0066] Step S2: Preparation of antistatic polyamide fabric:

[0067] Add 2.0 g of modified antistatic additive and 23 g of conductive fiber to 500 mL of tetrahydrofuran, and after ultrasonic dispersion, adjust the pH value to 4 with hydrochloric acid, and react at 55 ° C for 1.5 h. After filtering, washing and drying, combing and twisting to form yarn, and then interweaving by warp and weft to obtain antistatic polyamide fabric.

[0068] Example 9

[0069] This embodiment provides a production process of an antistatic polyamide fabric, comprising the following steps:

[0070] Step S1, preparation of conductive fibers:

[0071] 3 g of the modified graphene obtained in Example 3 was added to 500 mL of deionized water, and after ultrasonic dispersion, 30 g of polyamide fiber was added. After mixing evenly, the pH value was adjusted to 4 with hydrochloric acid, and then stirred for reaction at 80° C. for 2 h. After filtering, washing, and drying, a conductive fiber was obtained.

[0072] Step S2: Preparation of antistatic polyamide fabric:

[0073] Add 2.3 g of modified antistatic additive and 25 g of conductive fiber to 500 mL of tetrahydrofuran, and after ultrasonic dispersion, adjust the pH value to 5 with hydrochloric acid, and react at 60 ° C for 2 h. After filtering, washing and drying, combing and twisting to form yarn, and then interweaving by warp and weft to obtain antistatic polyamide fabric.

[0074] Comparative Example 3

[0075] Compared with Example 8, the difference is that the modified graphene prepared in Comparative Example 1 is used, and the other raw materials and steps are the same.

[0076] Comparative Example 4

[0077] Compared with Example 8, the difference is that the modified graphene prepared in Comparative Example 2 is used, and the other raw materials and steps are the same.

[0078] Comparative Example 5

[0079] Compared with Example 8, the difference is that the modified antistatic auxiliary agent is replaced by an equal amount of a commercially available antistatic finishing agent, and the other raw materials and steps are the same.

[0080] Performance tests were performed on Examples 7 to 9 and Comparative Examples 1 to 3. Washing resistance test: Referring to GB / T 3921-2008, the antistatic performance was tested before and after washing 10 times; Antistatic performance test: The sample was made into a test specimen with a specification of 45 mm × 45 mm, referring to GB / T 12703.1-2008, the test temperature was set to 20°C, the relative humidity was (35±5)%, the discharge voltage was 10 kV, the test time was 30 s, and the electrostatic half-life of the sample surface was recorded. The shorter the half-life, the better the antistatic performance; Moisture absorption performance test: Referring to GB / T 9995-1997, the humidity was adjusted for 24 hours at a temperature of 20°C and a relative humidity of (65±2)%, and the moisture regain was tested and calculated. The results are shown in Table 1:

[0081] Table 1

[0082]

[0083] It can be seen from Table 1 that the electrostatic half-life of the polyamide fabrics prepared by modified graphene and modified antistatic additives in Examples 7-9 is significantly shorter than that in Comparative Examples 3-5, and has good antistatic properties. After washing 10 times, the antistatic performance can still reach Class A standard (half-life ≤ 2s), has good wash fastness, and the moisture regain can reach up to 9.2%, and has good hygroscopicity; in addition, compared with Comparative Examples 3 and 5, the electrostatic half-life of Example 8 is smaller, indicating that the polyamide fabric prepared by modified graphene and modified antistatic additives has better antistatic properties.

[0084] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0085] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A production process for antistatic polyamide fabric, characterized in that: The following steps are involved: Step S1: adding modified graphene to deionized water, and then adding polyamide fiber after ultrasonic dispersion, and mixing evenly, adjusting the pH value to 3-4 with hydrochloric acid, and then stirring and reacting at 70-80° C. for 1-2 hours, and then filtering, washing, and drying to obtain conductive fiber; Step S2: adding a modified antistatic additive and conductive fiber to tetrahydrofuran, and then adjusting the pH value to 3-5 with hydrochloric acid after ultrasonic dispersion, and reacting at 50-60° C. for 1-2 hours, filtering, washing, and drying, and then combing and twisting to form yarn, and then interweaving the warp and weft to obtain an antistatic polyamide fabric.

2. The production process of an antistatic polyamide fabric according to claim 1, characterized in that: In step S1, the usage ratio of deionized water, modified graphene and polyamide fiber is 500 mL: 0.5-3 g: 25-30 g; in step S2, the usage ratio of tetrahydrofuran, modified antistatic additive and conductive fiber is 500 mL: 1.6-2.3 g: 20-25 g.

3. The production process of an antistatic polyamide fabric according to claim 1, characterized in that: The modified graphene is prepared by the following steps: A1. Add p-aminoazobenzene-4-sulfonic acid and sodium nitrite to deionized water, mix well, cool to 0-5°C, add concentrated hydrochloric acid dropwise, perform diazotization reaction at 0-5°C for 2-3h, add graphene aqueous dispersion, pre-react at 5-10°C for 2h, and then react at room temperature for 7-9h. After filtering, washing with anhydrous ethanol and drying, an intermediate is obtained. A2. Add the intermediate to the ethanol solution of zinc acetate, stir and immerse for 15-20 minutes, filter and dry, place in deionized water, add zinc acetate and hexamethylenetetramine after ultrasonic dispersion, react at 80-90° C. for 1-3 hours, filter, wash and dry to obtain modified graphene.

4. The production process of an antistatic polyamide fabric according to claim 3 is characterized in that: The usage ratio of the deionized water, p-aminoazobenzene-4-sulfonic acid, sodium nitrite, concentrated hydrochloric acid and graphene aqueous dispersion is 50 mL: 2.5-3.1 g: 0.8 g: 8.4-9.3 mL: 60 mL.

5. The production process of an antistatic polyamide fabric according to claim 3, characterized in that: The usage ratio of the zinc acetate ethanol solution, the intermediate, deionized water, zinc acetate and hexamethylenetetramine is 40 mL: 13.3-15.6 g: 80 mL: 5.2-7.6 g: 1-2 g; the concentration of the zinc acetate ethanol solution is 4.39-5.12 wt %.

6. The production process of an antistatic polyamide fabric according to claim 3, characterized in that: The graphene aqueous dispersion is prepared by dispersing sodium dodecylbenzene sulfonate and graphene in 150 mL of deionized water at a mass ratio of 60:12.7-14.3, followed by ultrasonic treatment for 30 minutes.

7. The production process of an antistatic polyamide fabric according to claim 1, characterized in that: The modified antistatic auxiliary agent is prepared by the following steps: Add acrylonitrile, glycidyl methacrylate, allyl polyoxyethylene ether and sodium p-styrene sulfonate to acetonitrile, stir and mix, add azobisisobutyronitrile, react at 70°C for 2-3h, and after rotary evaporation, cooling and solidification, grinding, eluting with anhydrous ethanol, and drying, obtain a modified antistatic additive.

8. The production process of an antistatic polyamide fabric according to claim 7, characterized in that: The dosage ratio of the acetonitrile, acrylonitrile, glycidyl methacrylate, allyl polyoxyethylene ether, sodium p-styrene sulfonate and azobisisobutyronitrile is 80 mL: 6.7-7.4mL: 13.5-14.2mL: 9.2-9.6mL: 20.6-21.2g: 1.2g.

9. An antistatic polyamide fabric, characterized in that: Prepared according to the production process according to any one of claims 1 to 8.